PENGARUH PERTUMBUHAN EKONOMI SEKTOR PRIMER, SEKUNDER, DAN TERSIER TERHDAP PENYERAPAN TENAGA KERJA DI KABUPATEN KOLAKA TIMUR - Tondi, La; Millia, Heppi; Tajuddin, Tajuddin; Yuniarmi, Yuniarmi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research is entitled The Effect of Economic Growth in the Primary, Secondary, and Tertiary Sectors on Labor Absorption in East Kolaka Regency. This research aims to find out and analyze the influence of economic growth in the primary sector, secondary sector and tertiary sector on labor absorption in East Kolaka Regency. This research is quantitative research using secondary data for the period 2014-2022 sourced from BPS, government publications and related books, and using the SPSS program. The data analysis used is simple linear regression The results of this research show that economic growth in the primary sector, secondary sector and tertiary sector has an effect on labor absorption. The partial test results show that the variable that has a positive and significant effect on labor absorption is the primary sector. Meanwhile, the secondary sector and tertiary sector have a positive but not significant effect. on labor absorption in East Kolaka Regency